“Confesso que chegar em casa e assistir lives não é fácil”: uma análise textual-interativa de concepções de formação continuada (re)produzidas por professores de língua portuguesa em evento de formação online - Anderson Carnin; Ana Isabel Eltz Dornelles; Caio Mira (Revista Odisséia)
This article aims to analyze the different conceptions of continuing education that are produced in a live broadcast destinated to Portuguese language teachers of the Rio Grande do Sul state’s system of education. In order to do so, this research articulates notions from the field of Applied Linguistics and Education, especially in relation to (continuing) teacher education, the notions of interactive framework, originating from Interactional Sociolinguistics, and reference, coming from Textual Linguistics, with the purpose to a textual-interactive analysis of the meanings regarding the notion of continuing training co-constructed by the participants of the teacher’s education event analyzed. This is a qualitative research, with an interpretive bias, focusing on the analysis of referencing as a linguistic-interactional phenomenon. The corpus of analysis is constituted by verbalizations (oral and written) produced by trainers and teachers in training in an online teacher education event, held in August 2022. The analysis undertaken reveals negotiations around the meanings of continuing education, sometimes understood from a perspective of technical rationality, and others from a perspective of practical rationality, and reinforces the contributions of the study of reference to the qualification of linguistic-interactional practices developed in the continuing education of Portuguese language teachers.